A infiltração de agentes e a ação controlada como formas de repressão ao crime organizado - Almeida, Fernando Cezar Bourgogne de (2010)
In this dissertation, there is a deeper approach in the study of controlled action and undercover agents, which are used as investigative means forseen within the Brazilian legislation to battle organized crime. To provide a better comprehension of the subject, this work begins with an analysis of the Democratic State of Law, and the necessity of that and its need for efficiency related to the counter attack of organized crime, therefore enabling a better comprehension of the subject. This type of crime, even though it is not a recent phenomena, has evolved altogether with the improvements from the communication means. This such criminals have had their power, business structure increased, they have also become transnational businesses. Therefore, it is necessary to understand the characteristics and features of this evolution: understanding the organized crime and knowing the resources there are available for its counter strike, some of them which are foreseen in international agreements which were incorporated in our justice ruling. With those concepts established, a more profound analysis becomes feasible for those investigative means that were chosen, their approach in other countries, the requirements necessary for utilization and the full gamut of operational resources that are imperative to confront criminal organizations